Medical Photography: Documentation, Art, and the Expression of Human Emotions - Elisabeth Aberer; Werner Stieber; Donja Homayoon; Regina Fink-Puches; Roland Lichen; Wolfgang Salmhofer; Alexandra Gruber-Wackernagel; Werner Aberer (Case Reports in Dermatology, 2016)
Medical photography is the state of the art for the documentation of dermatological disease. Experienced photographers take pictures of the most typical skin lesions in order to assist the clinician in assessing disease morphology and activity. In this study, we present 6 individuals with a variety of dermatoses and the expression of the patients’ emotions. The patients were asked to show their diseased skin and to present typically involved areas in the respective disease. The feelings expressed by their body movements and positions are viewed and interpreted. The patients’ history will be reported retrospectively. The aim of the report is to show that the art of medical photography does not only document skin lesions but also the disease burden and the associated impairment of quality of life. Moreover, dermatologic photography is a sensitive intervention for patients viewed in the light of teaching and patient care.